Hume's refutation of the cosmological argument - Campbell, Joseph K. (International journal for philosophy of religion, 1996)
Let me summarize the results of this paper in a way that seems fitting to Hume's discussion of the cosmological argument. There are some philosophers who adopt the most stringent empiricist principles. Such men and women would reject any notion of necessity that is not analytic, and for this reason they would never admit a proof of the necessary existence of anything. Other philosophers, though empiricists, are not so dogmatic. They question the need for, not the coherence of, necessary existence. They believe that the material universe is nothing over and above the sum of its material parts and, thus, see no reason to conclude that a necessary being exists based on PSR. Still others are driven by a rationalist persuasion. They would gladly recognize the existence of almost anything provided it be proven by reason and argument. When they confront the cosmological argument they do indeed find it compelling but still see no reason to conclude that God, or any transcendent being, necessarily exists. The entity established need be nothing more than the universe itself. Therefore, as Hume has demonstrated, no philosopher need accept the conclusion of the cosmological argument.